Semantic mechanisms may be responsible for developing synesthesia - Mroczko-Wąsowicz, Aleksandra; Nikolić, Danko (Frontiers in Human Neuroscience, 2014)
Currently, little is known about how synesthesia develops and which aspects of synesthesia can be acquired through a learning process. We review the increasing evidence for the role of semantic representations in the induction of synesthesia, and argue for the thesis that synesthetic abilities are developed and modified by semantic mechanisms. That is, in certain people semantic mechanisms associate concepts with perception-like experiences—and this association occurs in an extraordinary way. This phenomenon can be referred to as “higher” synesthesia or ideasthesia. The present analysis suggests that synesthesia develops during childhood and is being enriched further throughout the synesthetes’ lifetime; for example, the already existing concurrents may be adopted by novel inducers or new concurrents may be formed. For a deeper understanding of the origin and nature of synesthesia we propose to focus future research on two aspects: i) the similarities between synesthesia and ordinary phenomenal experiences based on concepts, and ii) the tight entanglement of perception, cognition and the conceptualization of the world. Most importantly, an explanation of how biological systems get to generate experiences, synesthetic or not, may have to involve an explanation of how we form semantic networks in general and what their role is in our ability to be aware of the surrounding world.